Sizka Irdianti Literature Review: Standardization of the Quality of Medicinal Plants and Leaf Extracts Based on Specific and Non-Specific Parameters - Sizka Irdianti; Alifah Salsabila; Vina Vina; Syifa Aulia Putri; Yonathan Tri Atmodjo Reubun (STIKes Medistra Indonesia, 2026)
Medicinal plants have long been used by the Indonesian people, passed down through generations, in various forms of traditional preparations. Leaves are one of the most commonly used parts of plants as raw materials for herbal medicines because they are rich in secondary metabolites such as flavonoids, alkaloids, tannins, and saponins. To ensure the quality, safety, and efficacy of traditional medicinal raw materials, a standardization process is required that adheres to the Indonesian Herbal Pharmacopoeia (FHI) and the Indonesian Materia Medica (MMI) through testing of specific and non-specific parameters. This literature review aims to compare and analyze the results of specific and non-specific parameter tests of ten types of crude drug materials and leaf extracts from medicinal plants, namely Kersen leaves (Muntingia calabura L.), Kawau leaves (Millettia sericea), Avocado leaves (Persea americana Mill.), Moringa leaves (Moringa oleifera), Lotus Leaf (Nelumbium nelumbo D.), Senggani Leaf (Melastoma malabathricum L.), Matoa Leaf (Pometia pinnata JR & G.Forst), Bidara Leaf (Ziziphus nummularia), Gatal Leaf (Laportea decumana (Roxb.) Wedd), and Dandang Gendis Leaf (Clinacanthus nutans). A literature search was conducted via the Google Scholar database using the keywords “Leaf Extract,” “Specific,” and “Non-Specific,” with the criterion that journals were published between 2018 and 2025. The review results indicate that most specific parameters—including organoleptic properties, phytochemical screening, and water-soluble and ethanol-soluble extract content—met the established standards. Meanwhile, for non-specific parameters—including moisture content, drying loss, total ash content, acid-insoluble ash content, heavy metal contamination, and microbial contamination—most results met the requirements, although some parameters in certain plants still exceeded the specified limits. This review provides a comprehensive overview of the standard quality ranges for medicinal plants and serves as a reference for the development of standardized herbal medicines in Indonesia.